Minecraft : Guide to survival - Milton, Stephanie; Marsh, Ryan (New York : Del Rey, 2020)
Introduces the game, outlines basic features, and describes such elements as hostile mobs, naturally generated structures, and biomes.
Introduction -- The technical stuff -- This is you -- Key -- Before you spawn -- The minecraft landscape -- Mobs -- Survival.
"Updated edition of Guide to exploration"--Cover.
Keywords: Minecraft (Game) -- Handbooks, manuals, etc -- Juvenile literature; Video games -- Handbooks, manuals, etc -- Juvenile literature; Juvenile literature; Illustrated works; Handbooks and manuals